Assessment of blood pressure and lipid profile in 1–5 years stunted children attending a tertiary care hospital - Deka, Anupama; Barman, Diganta; Ray, Prajnan Sankar (Indian Journal of Child Health, 2020)
Introduction: The prevalence of coronary artery disease (CAD) is rapidly increasing worldwide, particularly affecting low- and middle-income countries with high burden of malnutrition. Childhood stunting signifies chronic undernutrition in early life. There is an increased risk of metabolic alterations, namely, poor glycemic control, hypertension, and altered lipid profile that occur in children with stature deficit. Long-term effect of these metabolic alterations may predispose these undernourished children to an increased risk of CAD in future life. Aim: This study aims to assess the blood pressure (BP) and lipid profile in stunted children in the age group of 1–5 years. Materials and Methods: The present study was conducted in a tertiary care hospital in eastern region of India. The study comprised 65 stunted children (with height for age [HFA] <?2 standard deviation [SD]) in the cases group and 65 children with normal height and weight as control in the age group of 12 months. Detailed history and physical examination were recorded in a pretested pro forma. BP was recorded with a mercury sphygmomanometer with proper cuff. A 4-h fasting blood sample was collected for analysis of serum lipid profile. Results: Among the cases, 70% of children had HFA <?2SD and 30% had HFA<?3SD. The prevalence of elevated BP (particularly diastolic) among the study group was significantly higher than the controls (28% and 6%, respectively) (p=0.006). The mean serum triglyceride was significantly higher (p<0.001) and mean high-density lipoprotein was significantly lower in the case group (p<0.001) than the control group. Conclusion: The metabolic changes associated with stunting pose a threat for future cardiovascular disease. Early detection and prevention of stunting and its consequences will decrease the risk of cardiovascular morbidity and mortality in future life.